Implementation of Religious Culture in Instilling Islamic Values at Al-Atiqiyah Islamic Junior High School - Sri Nurpuspa Wahyuni; Siti Zahra Tsania Rahmah; Nenah Haryati; Adi Rosadi (LECTURES: Journal of Islamic and Education Studies, 2025)
The inculcation of Islamic values through the implementation of a religious culture in schools is essential for shaping students’ character. However, a gap still exists between religious learning practices and the internalization of religious values in students’ daily lives. This study aims to describe and analyze how religious culture is applied to instill Islamic values at SMP IT Al-Atiqiyah. Using a qualitative case study approach, data were collected through one-day observations, interviews with teachers and students, and document analysis. The findings reveal that religious culture is implemented through habituation of religious activities, teacher role modeling, and creating a school environment that supports religious practices. Teachers play a key role as exemplars in internalizing Islamic values, while students actively participate in routine religious activities. The study concludes that consistent implementation of religious culture effectively shapes students’ religious character. The implication is that a religious cultural approach can serve as a practical strategy for contextual and sustainable Islamic character education in Islamic-based secondary schools.